ANALISIS PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI COFFEE SHOP “RETORIKA KOPI” BANGKALAN - Masita, Siti; Suprapti, Isdiana; Wijayanti, Dian Eswin; Sunyigono, Andrie K. (Universitas Islam Madura, 2024)
Retorika Kopi is one of the coffee shops that emerged in the midst of intense competition with many businesses in the same field. The purpose of the study was to determine the attributes that consumers consider most in making purchases at Retorika Kopi, and to determine the stages of consumers in making purchasing decisions at Retorika Kopi. The sample used was 100 respondents who were calculated using the Cochran formula. The data was analyzed using validity test, reliability test, and fishbein analysis. The results showed that in deciding to buy at Retorika Kopi, the service attributes, facilities, and atmosphere have a positive value, while the price attribute has a neutral consumer attitude value. The process of making purchasing decisions at Retorika Kopi is carried out through the stages of need recognition, information search, evaluation, purchase and post-purchase processes. Updating and maintaining coffee shops, providing live music performances or interesting events at certain times are things that can be recommended to provide a comfortable atmosphere for consumers.